ChatGPT in the university classroom: perceptions, perceived usefulness and use intentions among undergraduate students - Vidnay Noel Valero-Ancco; Yolanda Lujano-Ortega (Institute of Advanced Engineering and Science, 2026)
The objectives of the present study are to analyze university students’ perceptions of and attitudes toward ChatGPT as a support tool for learning, as well as the user profiles derived from their technological acceptance, were analyzed. A quantitative, nonexperimental and cross-sectional design was applied to a non-probabilistic convenience sample of 438 undergraduate students, and a validated questionnaire composed of three dimensions compatibility with learning styles, ease of use and perceived usefulness, and continued use intentions was used. The data were analyzed with hierarchical cluster analysis (Ward method). The results reveal three groups of users: i) enthusiasts, with highly favorable perceptions and high use intentions; ii) moderate users, who exhibit partial acceptance; and iii) critical or disconnected users, who have a negative view of the tool. Taken together, the findings confirm that perceived usefulness, ease of use and trust are determining factors in the intention to use ChatGPT. This study provides empirical evidence on the diversity of attitudes toward generative artificial intelligence (GenAI) in university contexts and highlights the need to promote institutional strategies of critical digital literacy and teacher training for its ethical and pedagogical integration.